Impact of Environmental Conditions on Rice Farming Productivity and Efficiency in Bangladesh (International Journal of Statistical Sciences, 2026)
Rice farming plays a critical role in ensuring food security and economic stability in Bangladesh, with environmental conditions significantly affecting its productivity and efficiency. This study assesses the impact of climatic, soil and ecological factors on the performance of three major rice varieties Aus, Aman and Boro using secondary data from 1980 to 2021. Data Envelopment Analysis (DEA) was employed to estimate technical efficiency and Total Factor Productivity (TFP) growth while Tobit regression models were used to quantify the influence of environmental variables including average temperature, rainfall, humidity, sunshine and wind speed, under both Constant Returns to Scale (CRS) and Variable Returns to Scale (VRS) assumptions. The results revealed that average temperature showed a significant positive effect on all rice types under both CRS (β = 0.3356, p < 0.001) and VRS (β = 0.0813–0.1949, p < 0.05) models. Rainfall slightly improved Aman efficiency under CRS (β = 0.0001, p < 0.05) and had mixed effects under VRS positive for Aus (β = 0.0013, p < 0.10) but negative for Aman (β = –0.0027, p < 0.05). Humidity decreased Aus and Aman efficiency under CRS (β = –0.1001 and –0.0531, p < 0.01) but enhanced Boro under VRS (β = 0.0224, p < 0.05). Sunshine reduced efficiency for Boro (β = –0.1699, p < 0.001) and Aman (β = –0.1953, p < 0.001), while wind speed had negative effects on Aus and Aman under CRS (β = –0.1563 and –0.1971, p < 0.05) and a positive impact on Aus under VRS (β = 0.3719, p < 0.05). These findings underscore the differential sensitivity of rice varieties to environmental fluctuations and provide valuable insights for climate-resilient rice production and sustainable agricultural policymaking in Bangladesh.IJSS, Vol. 26(1), March, 2026, pp 39-51